(untitled) (REMUNOM, 2024)
Psychonephrology is the psychology field that focuses on psychological practices in the context of nephropathy. This stressful and exhausting context, not yet explored by psychology researchers, impacts not only physical but also psychological health. Moreover, like other areas of study, it is influenced by a country’s political and social events. In particular, the crisis in Brazilian dialysis care, aggravated by the COVID-19 pandemics, will be addressed here. This paper aims to report how kidney patients’ experiences were impacted by the country’s dialysis crisis. For this, a qualitative study-type experience report was used. Health psychology, hospital psychology, and nephrology were the main theoretical bases. In conclusion, it is highlighted that psychonephrology practice is intricately linked to health policies, and an integrated approach is not possible without considering such variables.